Hydrogen bond dynamics at water/Pt interfaces - Videla, Pablo Ernesto (2016)
We present results from computer simulations that shed light on structural and dynamic characteristics of hydrogen bonding of aqueous phases at ambient conditions, at the close vicinity of electrified metal interfaces. Our simulation strategy relied on the consideration of a Hamiltonian that explicitly incorporates effects from polarization fluctuations at the metal surface, induced by the instantaneous local electric field promoted by the partial charges at the solvent molecules. Compared to bulk environments, our results reveal important modifications in the hydrogen bond architectures that critically depend on the atomic arrangements of the interfaces exposed to the liquid phases and the net charges allocated at the metal plates. These modifications have equally important consequences on the characteristic time scales describing the ruptures of hydrogen bonds which are operated by mechanisms which are absent in descriptions that omit atomic detail and polarization fluctuations at the metal plates. We also analyze how the latter modifications are translated into spectral shifts in the stretching bands of infrared spectra of water adlayers.